Design Space Exploration of Energy Efficient NoC-and Cache-Based Many-Core Architecture - Souza, Matheus A.; Freitas, Henrique C.; Méhaut, Jean-François (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD); 2018: Anais do XXX International Symposium on Computer Architecture and High Performance Computing, 2018)
Performance of parallel scientific applications on many-core processor architectures is a challenge that increases every day, especially when energy efficiency is concerned. To achieve this, it is necessary to explore architectures with high processing power composed by a network-on-chip to integrate many processing cores and other components. In this context, this paper presents a design space exploration over NoC-based manycore processor architectures with distributed and shared caches, using full-system simulations. We evaluate bottlenecks in such architectures with regard to energy efficiency, using different parallel scientific applications and considering aspects from caches and NoCs jointly. Five applications from NAS Parallel Benchmarks were executed over the proposed architectures, which vary in number of cores; in L2 cache size; and in 12 types of NoC topologies. A clustered topology was set up, in which we obtain performance gains up to 30.56% and reduction in energy consumption up to 38.53%, when compared to a traditional one.